ENVIRONMENTAL RISK ANALYSIS IN MAGROVE AND CRAB CONSERVATION AREAS IN PAMUSIAN VILLAGE DUE TO LAND USE CHANGE IN TARAKAN CITY - Ahmad Hadian Pratama Hamzah; Marzuki Marzuki; Nurhasanah Nurhasanah; Subekti Nurmawati (Jurnal Ilmiah Global Education, 2023)
Mangroves are one of the largest coastal ecosystems in Indonesia that provide ecosystem functions and services for terrestrial biota, sea, seagrass ecosystems - coral reefs, and surrounding areas. Indonesia has the largest mangrove area in the world with an area of 22.6%, so that Indonesian mangroves contribute significantly to the absorption of carbon dioxide (CO2), one of the greenhouse gases. So that Indonesia's mangroves play an important role in regulating global climate change. The area of mangrove forests in Indonesia has declined sharply over the past two decades. The main drivers of mangrove degradation are use for settlement and cultivation. Currently, sustainable management is needed to maintain and improve the area and quality of mangroves. Mangrove forests are very important ecosystems for the conservation of fish resources. Mangroves are the habitat of fish, shrimp, crabs, and others. The ecological or biological function of mangrove ecosystems includes spawning grounds, foraging and breeding grounds for animals, especially fish, crabs and shrimp which are excellent commodities that benefit fishermen. Physically, mangrove forests prevent coastal abrasion, resist seawater intrusion and windbreaks, and reduce greenhouse gas emissions such as CO, CO2, SOx and NOx in the air and pollutants in coastal waters (Noor et al., 2006). The main factors of mangrove destruction are (1) pollution, (2) conversion of mangrove forests without considering environmental factors, and (3) excessive deforestation.